Ecofisiologia e modelo logístico na dinâmica de crescimento e desenvolvimento de soja em condições de excesso hídrico - Goergen, Patrícia Carine Hüller (2022)
Soybean is the main legume grown in the world. Rio Grande do Sul is an important national producer of the grain and the expansion of the crop to lowland areas where irrigated rice is traditionally cultivated in the state. The occurrence of excess water is harmful to the growth and development of plants, and compromises production, generating large losses of grain productivity. However, the duration of the stress, the phase of plant development and the weather conditions during the flood influence the severity of the stress. Thus, the present study aimed to evaluate the ecophysiology and characterize the growth of soybean cultivars by the logistic model subjected to flooding days in sowing seasons. To achieve this objective, two experiments were carried out at two sowing times (October and November) in the 2018/2019 and 2019/2020 crop years. The experimental design was completely randomized with four replications, each repetition consisting of a pot with one plant. Two soybean cultivars (NA 5909 RG and TEC IRGA 6070 RR) with relative maturity group close to 6.0 were used. The experiment I aimed to study the water excess in soybean cultivars in different phases of development during the vegetative phase and the experiment II, to study days of flooding in soybean cultivars, without and with a second flood from the vegetative phase V6-V7. In each experiment the following were determined: leaf area, dry mass, number of nodes, plant height, chlorophyll content and gas exchange measurements. The most sensitive phase to excess water for soybean cultivars is SE-EM, as there was no seed germination in both sowing dates and years studied. It was observed that the cultivar NA 5909 RG is more sensitive to excess water on days of flooding for the variables studied. For each group (3, 6, 9 and 12) of days of flooding evaluated, it was observed that when the soybean was submitted to a second flood it presented a worse performance than when only imposed to a single event of water stress, which shows no acclimatization. The second sowing season potentiated the effect of water stress on soybeans due to higher average air temperatures. The logistic model was adjusted to the leaf area variable, as a function of the accumulated degree-days. Leaf area can be estimated from models of relationship with mean air temperature, through the accumulation of degree-days.